A simulation technique for designing next-generation information and communication systems based on off-the-shelf microwave electronics computer tool. (2018) - Belkin, M.E.; Golovin, V.; Tyschuk, Y.; Sigov, A.S.
We review our known, updated, and new models and simulation results using power microwave-electronics computer tool NI AWRDE to pursue advanced performances of key microwave photonics elements such as semiconductor laser, photodiode, two types of electro-optic modulator, and multichannel reflecting Bragg grating. Based on these, the models of three key microwave photonics devices that fulfil basic processing procedures of a microwave-band network: signal oscillation, frequency conversion, and super-wide bandwidth photonic beam forming for phased array antenna, were introduced and studied. As a result, we proposed and validated experimentally a new approach to model a broad class of promising analogue microwave radio-electronics systems based on microwave photonics technology.